2015
DOI: 10.5830/cvja-2015-045
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors among patients with chronic kidney disease attending a tertiary hospital in Uganda

Abstract: IntroductionChronic kidney disease (CKD) is a risk factor for the development of cardiovascular disease, which is the primary cause of morbidity and mortality in patients with CKD. Local data about cardiovascular risk factors among CKD patients is generally scanty.ObjectiveTo determine the prevalence of the common cardiovascular risk factors among patients with CKD attending the nephrology out-patient clinic in Mulago national referral hospital in Uganda.MethodsThis was a cross-sectional study in which 217 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 16 publications
2
26
1
2
Order By: Relevance
“…Cardiovascular risk factors such as hypertension, diabetes mellitus, anemia, calcium-phosphate abnormalities, hyperuricemia, and left ventricular hypertrophy are highly prevalent in CKD. 9 , 10 These are largely responsible for cardiovascular disease burden and some complications in CKD patients. Management of these cardiovascular diseases and risk factors is important in retarding progression of CKD and reducing mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular risk factors such as hypertension, diabetes mellitus, anemia, calcium-phosphate abnormalities, hyperuricemia, and left ventricular hypertrophy are highly prevalent in CKD. 9 , 10 These are largely responsible for cardiovascular disease burden and some complications in CKD patients. Management of these cardiovascular diseases and risk factors is important in retarding progression of CKD and reducing mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of obesity in this series (11.4%) was similar to Babua's study (10.1%). 12 This obesity rate is lower than the one of Gorostidi's study (22.6%) and in Parikh's one (29.3%). 15,20 Jaroszynski's study showed the existence of a relationship between incidence of CKD and obesity (p<0.001).…”
Section: Discussionmentioning
confidence: 49%
“…11 The average age of CKD patients with CVD varies according to the study: 42 years in Uganda, 45 years Cameroon, 47 years in Brazil and 48 years in China. 7,[12][13][14] In this study, the average age was 59 years. However, the predominance of men is observed in almost all series: 51% in Uganda, 71% in Cameroon, 69% in Brazil, 59% in China and 60% in this series.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations